2016
DOI: 10.1039/c6nr00880a
|View full text |Cite
|
Sign up to set email alerts
|

2D-MoO3nanosheets for superior gas sensors

Abstract: By taking advantages of both grinding and sonication, an effective exfoliation process is developed to prepare two-dimensional (2D) molybdenum oxide (MoO3) nanosheets. The approach avoids high-boiling-point solvents that would leave a residue and cause aggregation. Gas sensors fabricated using the 2D-MoO3 nanosheets provide a significantly enhanced chemical sensor performance. Compared with the sensors using bulk MoO3, the response of the 2D-MoO3 sensor increases from 7 to 33; the sensor response time is reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 34 publications
3
112
0
Order By: Relevance
“…Amongst the main studied transition-metal oxides, zinc oxide (ZnO) and molybdenum oxides have attracted much attention for their potential application in lithium-ion batteries 56, 57 , supercapacitors 58 , dye removal 50, 51 , pigments 59 , gas sensors 60, 61 , and light emitting devices 62, 63 . In particular, ZnO has the potential for many applications due to its unique physical and chemical properties, such as high energy density, high electrochemical coupling coefficient, and broad range of radiation absorption 64 .…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the main studied transition-metal oxides, zinc oxide (ZnO) and molybdenum oxides have attracted much attention for their potential application in lithium-ion batteries 56, 57 , supercapacitors 58 , dye removal 50, 51 , pigments 59 , gas sensors 60, 61 , and light emitting devices 62, 63 . In particular, ZnO has the potential for many applications due to its unique physical and chemical properties, such as high energy density, high electrochemical coupling coefficient, and broad range of radiation absorption 64 .…”
Section: Introductionmentioning
confidence: 99%
“…The α-MoO 3 forming MoO 3−x can reduce the bandgap and enhance charge carrier mobility. Compared with the bulk MoO 3 , 2D-MoO 3 nanosheets had a better chemical sensor performance due to the 2D structure with a large surface area and more reactive sites [48] (see Figure 2f). Cheng et al [49] reported that MoO 3−x nanosheets can display strong LSPR from the visible to the near-infrared region, owing to the layered crystal structure, which could be used as highly efficient catalysts for the hydrogen generation from ammonia borane with visible light irradiation.…”
Section: The Morphology Of Nanostructured Moomentioning
confidence: 99%
“…For example, 2D MoO 3 exhibits a strong blue-shift when the lateral dimension reduces, as ascribed to the quantum size effect [44]. As a consequence, the strong quantum confinement effect leads to the enhanced band gap opening.…”
Section: Thin 2d Metal Oxidesmentioning
confidence: 99%
“…MoO 3 nanosheet samples were found to exhibit significantly enhanced alcohol vapor sensing performance compared to the bulk MoO 3 . It also was found that both the sensor response and recovery time were reduced significantly [44]. Sun et al described the synthesis of ultrathin two-dimensional transition metal oxide nanosheets [15].…”
Section: Thin 2d Metal Oxidesmentioning
confidence: 99%